TINJAUAN HUKUM KONTRAK ELEKTRONIK DALAM PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI (TRANSAKSI PEER TO PEER LENDING) - Nurhimmi Falahiyati (Universitas Quality, 2020)
The development of information technology has touched the Indonesian financial industry to make a big innovation in the financial world, where it is now possible for the process of lending and borrowing money that is different from conventional rules. Borrowers and lenders no longer need to come face to face in the transaction and lending process. Things like this are then commonly referred to as online loans. But of course, all developments will bring both positive and negative impacts. Are the transactions that occur in cyberspace valid and binding both parties involved in it, and whether the loan agreement has a contract in general which in conventional agreements is usually stated in written form. Therefore, the title was raised about how the legal review of electronic contracts in lending and borrowing money based on information technology.